Direct interactions with both p27 and Cdk2 regulate Spy1-mediated proliferation in vivo and in vitro. Issue 1 (2nd January 2016) - Al Sorkhy, Mohammad; Fifield, Bre-Anne; Myers, Dorothy; Porter, Lisa A.
ABSTRACT: Families of cyclin-like proteins have emerged that bind and activate cyclin dependent kinases (Cdk)s, directing the phosphorylation of noncanonical Cdk substrates. One of these proteins, Spy1, has demonstrated the unique ability to directly bind and activate both Cdk1 and Cdk2, as well as binding and promoting the degradation of at least one Cdk inhibitor, p27 Kip1 . Spy1 accelerates somatic cell growth and proliferation and is implicated in a number of human cancers including the breast, brain and liver. Herein we isolate key residues mediating the direct interaction with p27. We use mutants of Spy1 to determine the physiological role of direct interactions with distinct binding partners Cdk2 and p27. We demonstrate that disrupting the direct interaction with either Spy1 binding partner decreased endogenous activity of Cdk2, as well as Spy1-mediated proliferation. However, only the direct interaction with p27 was essential for Spy1-mediated effects on p27 stability. In vivo neither mutation completely prevented tumorigenesis, although each mutation slowed the rate of Spy1-mediated tumorigenesis and decreased overall tumor volumes. This work supports the conclusion that direct interaction with both p27 and Cdk2 contribute to Spy1-mediated effects on cell growth. It is important to elucidate the dynamics of these interactions and to consider these data when assessing functional outcomes.